Pengaruh Entrepreneurship Self-efficacy dan Entrepreneurship Leadership terhadap Work Readiness Siswa Konsentrasi Keahlian DKV SMKN 1 Lamongan: The Influence of Entrepreneurship Self-efficacy and Entrepreneurship Leadership on Work Readiness of Students of DKV Expertise Concentration at SMKN 1 Lamongan - Nur'run Fatihah; Tri Sudarwanto; Junaidi Budi Prihanto (ITScience (Information Technology and Science), 2025)
Self-efficacy plays an important role in determining their readiness to enter the competitive world of work. This study is expected to provide a clear picture of the relationship between the three variables and their impact on the work readiness of DKV students. This study uses a quantitative method with data collection through questionnaires distributed to students. The study results from the number of respondents were 100 (The number of respondents is 100). • Prob> F: 0.4597 (insignificant because p> 0.05). This shows that overall, the independent variables (self-efficacy and Et) of students of DKV expertise concentration of SMKN 1 Lamongan do not have a significant effect on the dependent variable (work readiness) Regress WorkReadiness Entrepreneurship Self Efficacy Entrepreneurship Leadership Every 1 unit increase in self-efficacy increases Work Readiness by 0.1051 points. However, this effect is not significant (p = 0.250 > 0.05) • Entrepreneurship Leadership (X2): o increases Entrepreneurship Readiness by 0.0665 points, but this effect is significant (p = 0.561 > 0.05). • Constant (_cons): o Coefficient: 4.2097 If all v. Overall, the regression model is not significant (Prob > F = 0.4597), which means that Entrepreneurship Self-efficacy and Entrepreneurship Leadership do not significantly affect Work Readiness. 2. The three independent variables have a minor influence on the dependent variable but are insignificant at the 98% confidence level (p > 0.05). 3. This model has a very low predictive ability (R-squared = 44%), so many other factors may significantly influence Work Readiness.